2023
DOI: 10.1371/journal.pbio.3002042
|View full text |Cite
|
Sign up to set email alerts
|

Breaking spore dormancy in budding yeast transforms the cytoplasm and the solubility of the proteome

Abstract: The biophysical properties of the cytoplasm are major determinants of key cellular processes and adaptation. Many yeasts produce dormant spores that can withstand extreme conditions. We show that spores of Saccharomyces cerevisiae exhibit extraordinary biophysical properties, including a highly viscous and acidic cytosol. These conditions alter the solubility of more than 100 proteins such as metabolic enzymes that become more soluble as spores transit to active cell proliferation upon nutrient repletion. A ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…Despite this difference, we have found evolutionarily conserved roles for the dynamic processes of polysome collapse and mRNA condensation in mediating stress-induced increased mesoscale macromolecular diffusivity within the cytoplasm (Figure 6). Several studies have demonstrated that decreases in ATP cause yeast or bacterial cells to transition to a glassy/solid state in the cytoplasm (Munder et al, 2016;Parry et al, 2014;Plante et al, 2023). In our study, we also found that the reduction of ATP and cytoplasmic pH results in decreased mesoscale diffusivity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Despite this difference, we have found evolutionarily conserved roles for the dynamic processes of polysome collapse and mRNA condensation in mediating stress-induced increased mesoscale macromolecular diffusivity within the cytoplasm (Figure 6). Several studies have demonstrated that decreases in ATP cause yeast or bacterial cells to transition to a glassy/solid state in the cytoplasm (Munder et al, 2016;Parry et al, 2014;Plante et al, 2023). In our study, we also found that the reduction of ATP and cytoplasmic pH results in decreased mesoscale diffusivity.…”
Section: Discussionsupporting
confidence: 80%
“…We found that the initial fluidization of the cytoplasm was important for the formation of Q-bodies. It will be interesting to investigate if other mesoscale assemblies that are known to assemble during ATP depletion (Marini et al, 2020;Munder et al, 2016;Plante et al, 2023) also require cytoplasmic fluidization for their formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest this may not be the case, since the provision of nutrients can promote the early onset polarized growth of poorly swollen spores whilst nutrient depletion can prevent germination of fully swollen spores ( Ekundayo and Carlile, 1964 ; Feofilova et al., 2012 ). More recently, the breaking of dormancy of spores of ascomycete yeasts has been shown to require reduction of the very high internal viscosity or “glassy state” of the spore cytoplasm due to the high internal concentration of compatible solutes such as trehalose ( Plante et al., 2023 ). The transition from a highly viscous to a more fluid cytoplasm more capable of metabolic activity is regulated by chaperones that enable the solubilisation and refolding of the spore proteome ( Plante et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…How do these dormant spores with limited metabolic activity transition from this nearly inactive state to a lively germling? A recent study published in PLOS Biology by Plante and colleagues shows that the proper transition is at least in part orchestrated by chaperones, specifically Hsp42 [6]. The authors show that this heat shock protein is activated by phosphorylation during very early stages of germination and ensures proper resolubilization of proteins during breaking of dormancy.…”
mentioning
confidence: 99%